In situ monitoring of particle fracture in aluminium alloys. Issue 3 (22nd September 2017) - Wisner, B.; Kontsos, A.
Abstract: Material damage at the microscale involves both initiation and interaction effects that are typically activated long before the appearance of macroscopically observable failure events. These early appearances of damage have been broadly classified as microstructure‐sensitive damage precursors or indicators. A particular class of such precursors which is of importance to aluminium and other precipitate‐hardened alloys is the focus of this article. Specifically, the hard, intermetallic particles in aluminium alloys fracture before significant failure occur in the surrounding matrix. In this investigation, an effort to directly assess particle fracture activity at the time and scale that it occurs is made by coupling mechanical testing inside a scanning electron microscope with nondestructive evaluation techniques including digital image correlation as well as real‐time acoustic emission monitoring. The use of a surface measurement technique along with a volumetric monitoring method at the microscope scale provides a way for coupling of fracture information at locations which are directly related to the particle activity. In this article, Al2024‐T3 specimens in the as‐received condition were subjected to tension as well as to tension‐tension cyclic loading. The obtained in situ results demonstrate, for the first time to the best knowledge of the authors, that particle fracture occurs early in the damage process which justifies its characterization as a material damage precursor. The overall approach provides datasets capable to detect particle fracture initiation, which could become useful in future structural health monitoring applications.